2010
DOI: 10.1016/j.comppsych.2009.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Eating disorder psychopathology as a marker of psychosocial distress and suicide risk in female and male adolescent psychiatric inpatients

Abstract: Objective-To examine psychosocial correlates of specific aspects of eating disorder (ED) psychopathology (i.e., dietary restriction, body dissatisfaction, binge eating, and self-induced vomiting) in psychiatrically-hospitalized adolescent girls and boys.Method-Four hundred and ninety-two psychiatric inpatients (286 girls and 206 boys), aged 12 to 19 years, completed self-report measures of psychosocial and behavioral functioning including measures of suicide risk and ED psychopathology. Associations between ED… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 50 publications
1
4
0
6
Order By: Relevance
“…One implication of this finding is that teaching youth high in SS how to calm negative affect may reduce smoking risk in situations in which they are experiencing negative affect. This may be a particularly important self-regulatory skill for high SS adolescents to develop, given that negative affect predisposes youth to multiple risk behaviors (e.g., McNamara, Swaim, & Rosén, 2010;Zaitsoff & Grilo, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…One implication of this finding is that teaching youth high in SS how to calm negative affect may reduce smoking risk in situations in which they are experiencing negative affect. This may be a particularly important self-regulatory skill for high SS adolescents to develop, given that negative affect predisposes youth to multiple risk behaviors (e.g., McNamara, Swaim, & Rosén, 2010;Zaitsoff & Grilo, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In clinical samples, approximately 30% of adults with BN symptoms have been found to self-report a history of childhood sexual abuse and greater than 50% of women with BN have been found to self-report a history of physical maltreatment [18,20,21,23,24]. Additionally, in longitudinal samples, all forms of childhood abuse, especially sexual abuse, have been noted to precede the development of BN-relevant symptoms including dietary restriction, laxative abuse, and self-induced vomiting [24,25,26,27]. …”
Section: Introductionmentioning
confidence: 99%
“…10,11 It appears that alexithymia may play an important role in binge eating disorder (BED), although data are still limited: specifically, patients with alexithymia may show higher levels of psychological distress than those without alexithymia and the presence of an alexithymic trait may be related to greater severity of BED. 12 It is widely recognized that individuals with EDs may be at risk for suicide, [13][14][15][16] but, to date, few studies have reported data on suicide risk among patients with BED. In fact, a recent meta-analysis found that data on BED (no suicides in a cumulative sample of 246 patients who were screened) were still based on too few studies to be considered clinically relevant.…”
mentioning
confidence: 99%